A non-classical approach to recommender system for competitive programmers - Chowdhury, Tahanima; Rafiq Ullah, Ahmed; Maqsud Ul Anwar, MD. (BRAC University, 2018)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.